CPS1-promoted the progression of lung adenocarcinoma via suppressing ammonia induced the activation of ROS/AMPK/P53/LKB1 signaling pathway - Yanchao Luan; Liru Liu; Jiakun Liu; Li Zhao; Chao Liang (Scientific Reports)
Abstract This study aims to explore how CPS1 influences the progression of lung adenocarcinoma by affecting the ammonia-induced ROS/AMPK/P53/LKB1 signaling pathway. Bioinformatics analysis was conducted to identify differential gene expression in lung adenocarcinoma patients. A549 cells were infected with control (NC) or CPS1 knockdown (CPS1-KD) lentivirus. Cells were treated with or without AMPK agonists, AMPK inhibitors, P53 agonists, or P53 inhibitors, followed by Western blot analysis of CPS1, NOX2, NOX4, p-AMPK, p-P53, and LKB1 protein levels. The content of MDA and SOD was measured, and the expression of AMPK, caspase-3 and P53 in tumor cells was detected through immunofluorescence. Apoptosis-related protein expression and tumor cell apoptosis were assessed using Western blot and flow cytometry. Tumor cell proliferation was evaluated using CCK-8 assays and colony formation experiments. Tumor size was measured in xenograft models using nude mice. Bioinformatics analysis indicated that LKB1 positively regulates AMPK activity. CPS1 knockdown results in increased ammonia levels, with upregulated expression of NOX2, NOX4, p-AMPK, p-P53, and LKB1 in tumor cells. Elevated P53 levels, along with significant increases in Bax, Caspase-8,and Caspase-12 expression, were observed, promoting apoptosis and inhibiting tumor cell proliferation. AMPK and P53 act to inhibit lung adenocarcinoma progression. CPS1 promotes the progression of lung adenocarcinoma by suppressing ammonia-induced activation of the ROS/AMPK/P53/LKB1 signaling pathway.